2015
DOI: 10.1242/dev.118604
|View full text |Cite
|
Sign up to set email alerts
|

Cellular analysis of cleavage-stage chick embryos reveals hidden conservation in vertebrate early development

Abstract: Birds and mammals, phylogenetically close amniotes with similar post-gastrula development, exhibit little conservation in their post-fertilization cleavage patterns. Data from the mouse suggest that cellular morphogenesis and molecular signaling at the cleavage stage play important roles in lineage specification at later (blastula and gastrula) stages. Very little is known, however, about cleavage-stage chick embryos, owing to their poor accessibility. This period of chick development takes place before egg-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 37 publications
(47 reference statements)
3
26
0
Order By: Relevance
“…Because the unubiquitous GFP expression could be driven by the CMV promoter, we also investigated p-pol II expression during the intrauterine stages and obtained similar results as reported in our previous study [52]. These data suggest that ZGA in chicken first occurs in the central cells between EGK stages II and III, and then expands toward the periphery; it does not occur simultaneously in all cells.…”
Section: Discussionsupporting
confidence: 75%
“…Because the unubiquitous GFP expression could be driven by the CMV promoter, we also investigated p-pol II expression during the intrauterine stages and obtained similar results as reported in our previous study [52]. These data suggest that ZGA in chicken first occurs in the central cells between EGK stages II and III, and then expands toward the periphery; it does not occur simultaneously in all cells.…”
Section: Discussionsupporting
confidence: 75%
“…Another notable feature of these embryos is that the point at which the first two cleavage furrows meet is not centered at the middle of the embryo (Sheng 2014; Nagai et al 2015). There is a known correlation between asymmetric inheritance of maternally deposited factors and establishment of PGCs, but whether this is associated with off-center early cleavages is unclear.…”
Section: Cellular Mechanisms Underlying Cell Cleavage Pattern Determimentioning
confidence: 99%
“…As cleavage progresses, the embryo will reach 5–6 layers of cells in thickness before thinning again during and after gastrulation (Sheng 2014). A study found that approximately 75 % of surface cells (i.e., those in the uppermost layer) divided in a direction parallel to the blastoderm plane, yielding two daughters in the same layer, while deeper cells show more variation, with approximately 56 % dividing in a direction 30–90° from that of the blastoderm plane (Nagai et al 2015; see below). These data suggest that cleavage orientation only partly explains increasing layer number, but other mechanisms, such as rearrangement of already cellularized blastomeres, may also be involved.…”
Section: Cellular Mechanisms Underlying Cell Cleavage Pattern Determimentioning
confidence: 99%
“…Additionally, developmentally constitutive HSP30 homologues in Xenopus were first detected in early and mid-tailbud embryos, after gastrulation, but not soon after ZGA, which in Xenopus occurs at the 128- to 256-cell stage7. It was recently discovered that ZGA starts between EGK stages II and III in chicken3233. HSP25 and HSP30CL transcripts were also not induced immediately after ZGA, at EGK III, but earlier than the homologues in Xenopus .…”
Section: Discussionmentioning
confidence: 97%